d-Chiro-Inositol extends the lifespan of male Drosophila melanogaster better than d-Pinitol through insulin signaling and autophagy pathways. - Du, X.; Wang, Y.; Wang, J.; Liu, X.; Chen, J.; Kang, J.; Yang, X.; Wang, H. (Experimental Gerontology, 2022)
d-Pinitol (DP) is the methylated product of d-Chiro-Inositol (DCI), which is one of the nine isomers of inositol with optical activity. Both substances possess antioxidant activity. This study was conducted to investigate and compare the antioxidant and life-prolonging effects of DCI and DP on male Drosophila melanogaster. Results showed that DCI and DP prolonged the lifespan and improved the climbing, anti-stress, and antioxidant activities. After treatment with DCI and DP, intestinal homeostasis was improved and the abnormal proliferation of intestinal stem cells (ISCs) was attenuated. Furthermore, real-time PCR revealed downregulated expression levels of PI3K and Akt and upregulated expression levels of Dilp5 and FOXO, which consequently activated Atg1, Atg5, Atg8a, and Atg8b and increased the number of lysosomes. Altogether, DCI exerts a slightly better effect than DP based on various indicators. RNAi D. melanogaster lifespan and molecular docking results further suggested that DCI and DP could prolong longevity through insulin signaling (IIS) and autophagy pathways.